Kinetics of Oxidation of Cysteine by Chloramine-B in HClO4 Medium - Demappa, T. (Asian Journal of Chemistry, 2010)
The kinetics of oxidation of cysteine by chloramine-B in HClO4 medium has been carried out at 30°C. The reaction rate shows a first order dependence each on [CAB] and [cysteine] and inverse fractional order on [H+]. Addition of halide ions, ionic strength, dielectric constant of the medium and the reduction product benzenesuJphonamide have no significant effect onthe reaction rate. Thermodynamic parameters have been evaluated.